A kind of impact-resistant large-particle PMMA composite material and acrylic sheet produced by using the same
By using TPU resin and polymethyl methacrylate composite shell layer in acrylic sheet and adding nanomaterials as toughening compositions, the problem of low impact toughness of existing acrylic sheets is solved, and high strength and flame retardant are achieved And lightweight impact-resistant large-particle PMMA composite material to meet the needs of decorative panels.
Patent Information
- Application Number
- CN202410590519.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-05-13
Smart Images

Figure GHA0000008734640000171 
Figure GHA0000008734640000181
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymethyl methacrylate composite materials, and in particular to an impact-resistant large-particle PMMA composite material and an acrylic sheet produced using the same. Background Art
[0002] Polymethyl methacrylate PMMA, commonly known as acrylic-plexiglass, has the advantages of good light transmittance, chemical corrosion resistance, weather resistance, green environmental protection, easy processing, easy cleaning, maintenance, light weight, low cost, etc. It is widely used in many fields such as construction, sanitary ware, transportation, decoration, medicine, fiber optic communications, etc.
[0003] Acrylic sheets are gradually entering the daily life of the public as a new organic decorative material. However, the acrylic sheets currently available on the market are cast with high-filling (45-60wt%) inorganic filler materials. Although they have the advantages of good chemical corrosion resistance, weather resistance, easy cleaning, easy maintenance, and low cost, they have low overall impact toughness and are relatively bulky. They are easy to crack under external impact and cannot meet the needs of cabinet panels and bathroom countertops. In order to solve the above problems, the inventor provides an impact-resistant large-particle PMMA composite material and an acrylic sheet produced using the same. Summary of the invention
[0004] In order to solve the technical problems in the prior art that acrylic sheets have low impact toughness and are relatively bulky, the present application provides an impact-resistant large-particle PMMA composite material and an acrylic sheet produced using the same.
[0005] The impact-resistant large-particle PMMA composite material provided in the present application is realized by the following technical solutions:
[0006] An impact-resistant large-particle PMMA composite material comprises a thermoplastic elastomer TPU resin as a core structure and a polymethyl methacrylate composite shell layer as a shell structure, wherein the polymethyl methacrylate composite shell layer is made of the following raw materials in parts by mass: 80-100 parts of methyl methacrylate, 4-8 parts of an emulsifier, 80-120 parts of deionized water, 0.2-0.35 parts of dibenzoyl peroxide, 1-4 parts of 2,2-diallyl-4-ene-1-amine, 1-10 parts of 1,6-hexanediol diacrylate, and 5-10 parts of a toughening composition; the toughening composition is composed of at least one of nano-boron nitride nanosheets, nano-titanium nitride with zinc oxide whiskers, graphene, carbon nanotubes, and halloysite nanotubes.
[0007] The impact-resistant large-particle PMMA composite material prepared in the present application has the advantages of good chemical corrosion resistance, weather resistance, easy cleaning and easy maintenance, and also has the advantages of good impact resistance, toughness and light weight, meeting the needs as a decorative panel.
[0008] Preferably, the polymethyl methacrylate composite shell layer is made of the following raw materials in parts by mass: 100 parts of methyl methacrylate, 5-6 parts of emulsifier, 100 parts of deionized water, 0.30-0.35 parts of dibenzoyl peroxide, 2.8-3.2 parts of 2,2-diallyl-4-ene-1-amine, 4-6 parts of 1,6-hexanediol diacrylate, and 6-8 parts of toughening composition.
[0009] Preferably, the toughening composition is composed of nano-boron nitride nanosheets, nano-titanium nitride, zinc oxide whiskers, and halloysite nanotubes.
[0010] Preferably, the mass ratio of the nano-boron nitride nanosheets, nano-titanium nitride, zinc oxide whiskers, and halloysite nanotubes is 6:(0.5-2):(0.5-1):2.
[0011] By adopting the above technical solution, the overall impact toughness and mechanical strength of the impact-resistant large-particle PMMA composite material can be improved, and the flame retardant property and flexural strength can also be improved.
[0012] Preferably, the thermoplastic elastomer TPU resin as the core structure contains unreacted double bonds, and is connected to the polymethyl methacrylate composite shell layer as the shell structure through double bond polymerization; the thermoplastic elastomer TPU resin with the core structure is at least one of spherical, quasi-spherical, and cylindrical; the thermoplastic elastomer TPU resin with the core structure is mainly made of diisocyanate, chain extender, polyol, catalyst, toughening filler, anti-aging agent, and inhibitor; the chain extender is at least one of 1,4-butanediol, 3-methyl-1,5-pentanediol, and 1,6-hexanediol in combination with 2,3-dihydroxy-1-butene, 4-cyclohexene-1,2-dimethanol, hexene-5-1,2-diol, and 3-hexene-1,6-diol. The invention discloses a novel thermoplastic elastomer (TPU) resin having a core structure and a hard segment content of 40-46 wt %; the catalyst is organic tin or organic bismuth; the toughening filler content is 4-8 wt %; and the toughening filler is composed of nano-aluminum oxide and zinc oxide whiskers.
[0013] By adopting the above technical solution, the impact-resistant large-particle PMMA composite material is endowed with good impact toughness.
[0014] Preferably, the production process of the impact-resistant large-particle PMMA composite material comprises the following steps:
[0015] S1, preparation of thermoplastic elastomer TPU resin with core structure: mix the chain extender and the polymerization inhibitor accounting for 25-40wt% of the total mass of the polymerization inhibitor and put them into the first feed tank of the twin-screw extruder; mix the polyol and the remaining polymerization inhibitor and put them into the second feed tank of the twin-screw extruder; mix the diisocyanate, catalyst, toughening filler and anti-aging agent and put them into the third feed tank of the twin-screw extruder; then extrude and granulate at 175-180°C, extrude, water-cool and granulate from the twin-screw extruder to obtain thermoplastic elastomer TPU resin pellets with a particle size of 0.5-5mm;
[0016] S2, methyl methacrylate, emulsifier, deionized water, dibenzoyl peroxide 2,2-diallyl-4-ene-1-amine, and 1,6-hexanediol diacrylate are mixed and treated with high-speed shear to obtain an emulsion, alkali solution is added dropwise to adjust the pH value to 9-10, the temperature is raised to 60-65° C. and reacted for 15-20 minutes until the system becomes milky white, and then a toughening composition is added and stirred at 200-240 rpm for 5-10 minutes, and then the thermoplastic elastomer TPU resin pellets prepared in S1 are added and reacted at 180-240 rpm and 60-65° C. for 5-10 minutes, the temperature is raised to 88-95° C. and ultrasonic dispersion is performed, and the reaction is continued for 30-45 minutes under stirring at 180-240 rpm and ultrasonic dispersion, and deionized water is removed by vacuum distillation to obtain a semi-finished impact-resistant large-particle PMMA composite material;
[0017] S3, the semi-finished impact-resistant large-particle PMMA composite material is placed at 82-85° C. for heat treatment for 20-24 hours to obtain a finished impact-resistant large-particle PMMA composite material.
[0018] The preparation method of the impact-resistant large-particle PMMA composite material provided in the present application is relatively simple, has low difficulty in implementation and operation, and is easy to realize industrial production and manufacturing, thereby reducing the production cost of the impact-resistant large-particle PMMA composite material.
[0019] The acrylic sheet produced by using the impact-resistant large-particle PMMA composite material provided in the present application is realized by the following technical solutions:
[0020] An acrylic sheet produced by using an impact-resistant large-particle PMMA composite material is made of the following raw materials in parts by mass: 10-20 parts of an impact-resistant large-particle PMMA composite material, 20-30 parts of an inorganic filler composition, 60-80 parts of methyl methacrylate, 1-5 parts of pentafluorophenyl methacrylate, 0.2-0.3 parts of dibenzoyl peroxide, 0.5-2 parts of γ-methacryloxypropyltrimethoxysilane, and 1-4 parts of 1,6-hexanediol diacrylate; the inorganic filler composition is composed of at least one of calcium carbonate, titanium dioxide, kaolin, aluminum hydroxide, and magnesium hydroxide, and at least one of hollow glass microspheres, halloysite nanotubes, nanoaluminum oxide, and zinc oxide whiskers.
[0021] The acrylic sheet prepared using the impact-resistant large-particle PMMA composite material in this application has the advantages of good chemical corrosion resistance, weather resistance, easy cleaning and easy maintenance. It also has the advantages of good impact resistance, toughness, antibacterial and mildew resistance, light weight and high strength, and can meet the use requirements as a decorative panel.
[0022] Preferably, the acrylic sheet is made of the following raw materials in parts by mass: 14-16 parts of impact-resistant large-particle PMMA composite material, 22-24 parts of inorganic filler composition, 65-70 parts of methyl methacrylate, 3-4 parts of pentafluorophenyl methacrylate, 0.25-0.3 parts of dibenzoyl peroxide, 1-1.5 parts of γ-methacryloxypropyltrimethoxysilane, and 3.0-3.5 parts of 1,6-hexanediol diacrylate; the inorganic filler composition is composed of ultrafine calcium carbonate, ultrafine titanium dioxide, hollow glass microspheres with a particle size D50 of 25-50 microns, halloysite nanotubes, and zinc oxide whiskers.
[0023] Preferably, the inorganic filler composition is composed of 2-5wt% zinc oxide whisker, 20-40wt% hollow glass microspheres with a particle size D50 of 25-50 microns, 5-10wt% halloysite nanotubes, 5-20wt% ultrafine mixed crystal titanium dioxide, and the balance is ultrafine calcium carbonate.
[0024] By adopting the above technical scheme, the prepared acrylic sheet is guaranteed to have good impact toughness, chemical corrosion resistance, and weather resistance, while also being endowed with good antibacterial and hygienic properties, wear resistance, light weight and easy processing properties, and flame retardant and safety properties.
[0025] Preferably, a method for producing an acrylic sheet using an impact-resistant large-particle PMMA composite material is as follows:
[0026] Step 1, preparation of impact-resistant large-particle PMMA composite material;
[0027] Step 2: Mix the inorganic filler composition, γ-methacryloxypropyltrimethoxysilane, and 1,6-hexanediol diacrylate to obtain a mixture A; and at the same time, mix methyl methacrylate, pentafluorophenyl methacrylate, and an impact-resistant large-particle PMMA composite material to obtain a mixture B;
[0028] Step 3, adding 40-60% of the total mass of dibenzoyl peroxide to the mixture B in step 2, mixing at 100-200 rpm for 5-10 min, heating to 80-85° C., mixing at 100-200 rpm for 25-40 min, and cooling to room temperature to obtain a PMMA prepolymer;
[0029] Step 4: Add mixed material A to the PMMA prepolymer and mix at 100-200 rpm for 30-60 minutes, cast it into a molding mold, ultrasonically vibrate it for 60-120 seconds, let it stand at room temperature for 0.5-1 hour, and then place it in an oven at 80-85°C for polymerization for 4-6 hours. Cool it, and demold it to obtain a high impact toughness acrylic sheet.
[0030] The method for preparing acrylic sheet using the impact-resistant large-particle PMMA composite material in the present application is relatively simple, has low difficulty in implementation, is easy to implement industrial production, and thus reduces the production cost of the acrylic sheet composite material.
[0031] In summary, this application has the following advantages:
[0032] 1. The impact-resistant large-particle PMMA composite material prepared in this application has the advantages of good chemical corrosion resistance, weather resistance, easy cleaning and easy maintenance. It also has the advantages of good impact resistance, toughness and light weight, meeting the needs of decorative panels.
[0033] 2. The preparation method of the impact-resistant large-particle PMMA composite material provided in the present application is relatively simple, has low difficulty in implementation, and is easy to realize industrial production and manufacturing, thereby reducing the production cost of the impact-resistant large-particle PMMA composite material.
[0034] 3. The acrylic sheet prepared using the impact-resistant large-particle PMMA composite material in this application has the advantages of good chemical corrosion resistance, weather resistance, easy cleaning and easy maintenance. It also has the advantages of good impact resistance, toughness, antibacterial and mildew resistance, light weight and high strength, and can meet the use requirements as a decorative panel.
[0035] 4. The method for preparing acrylic sheet using the impact-resistant large-particle PMMA composite material in this application is relatively simple, has low difficulty in implementation, and is easy to realize industrial production and manufacturing, thereby reducing the production cost of acrylic sheet composite materials. DETAILED DESCRIPTION
[0036] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.
[0037] Example
[0038] An impact-resistant large-particle PMMA composite material includes a thermoplastic elastomer TPU resin as a core structure and a polymethyl methacrylate composite shell layer as a shell structure. The thermoplastic elastomer TPU resin as the core structure contains unreacted double bonds and is polymerized and connected with the polymethyl methacrylate composite shell layer as the shell structure through double bonds. The thermoplastic elastomer TPU resin of the core structure is at least one of spherical, quasi-spherical, and cylindrical.
[0039] The polymethyl methacrylate composite shell layer is made of the following raw materials in parts by mass: 80-100 parts of methyl methacrylate, 4-8 parts of emulsifier, 80-120 parts of deionized water, 0.2-0.35 parts of dibenzoyl peroxide, 1-4 parts of 2,2-diallyl-4-ene-1-amine, 1-10 parts of 1,6-hexanediol diacrylate, and 5-10 parts of toughening composition.
[0040] The preferred formula of the polymethyl methacrylate composite shell layer is as follows: 100 parts of methyl methacrylate, 5-6 parts of emulsifier, 100 parts of deionized water, 0.30-0.35 parts of dibenzoyl peroxide, 2.8-3.2 parts of 2,2-diallyl-4-ene-1-amine, 4-6 parts of 1,6-hexanediol diacrylate, and 6-8 parts of toughening composition.
[0041] The toughening composition is composed of at least one of nano-boron nitride nanosheets, nano-titanium nitride, zinc oxide whiskers, graphene, carbon nanotubes, and halloysite nanotubes. Preferably, the toughening composition is composed of nano-boron nitride nanosheets, nano-titanium nitride, zinc oxide whiskers, and halloysite nanotubes, and the mass ratio of nano-boron nitride nanosheets, nano-titanium nitride, zinc oxide whiskers, and halloysite nanotubes is 6:(0.5-2):(0.5-1):2.
[0042] The core-structured thermoplastic elastomer TPU resin is made of diisocyanate, chain extender, polyol, catalyst, toughening filler, anti-aging agent and polymerization inhibitor 4-methoxyphenol MEHQ (about 0.05% of the total mass of the TPU resin).
[0043] The chain extender is composed of at least one of 1,4-butanediol, 3-methyl-1,5-pentanediol, and 1,6-hexanediol and at least one of 2,3-dihydroxy-1-butene, 4-cyclohexene-1,2-dimethanol, hexene-5-1,2-diol, 3-hexene-1,6-diol, 3-hexene-2,5-diol, and (9ci)-1-cyclohexene-1,3-diol.
[0044] The polyol is composed of terminal hydroxyl polybutadiene with a molecular weight of 500-2000 and at least one of polycarbonate diol with a molecular weight of 1000-2000, polyester diol with a molecular weight of 1000-2000, and polyether diol with a molecular weight of 1000-2000.
[0045] The total molar amount of active functional groups contained in the chain extender and the polyol is equal to 1.0-1.02 times the molar amount of -NCO in the diisocyanate, and the hard segment content in the thermoplastic elastomer TPU resin with a core structure is 40-46wt%.
[0046] The catalyst is organic tin or organic bismuth, specifically bismuth octanoate.
[0047] The toughening filler has a content of 4-8wt% and is composed of nano-aluminum oxide and zinc oxide whiskers in a mass ratio of 19:1.
[0048] A method for preparing an impact-resistant large-particle PMMA composite material comprises the following steps:
[0049] S1, preparation of thermoplastic elastomer TPU resin with core structure: mix the chain extender and the polymerization inhibitor accounting for 25-40wt% of the total mass of the polymerization inhibitor and put them into the first feed tank of the twin-screw extruder; mix the polyol and the remaining polymerization inhibitor and put them into the second feed tank of the twin-screw extruder; mix the diisocyanate, catalyst, toughening filler and anti-aging agent and put them into the third feed tank of the twin-screw extruder; then extrude and granulate at 175-180°C, extrude, water-cool and granulate from the twin-screw extruder to obtain thermoplastic elastomer TPU resin pellets with a particle size of 0.5-5mm;
[0050] S2, methyl methacrylate, emulsifier, deionized water, dibenzoyl peroxide 2,2-diallyl-4-ene-1-amine, and 1,6-hexanediol diacrylate are mixed and treated with high-speed shear to obtain an emulsion, alkali solution is added dropwise to adjust the pH value to 9-10, the temperature is raised to 60-65° C. and reacted for 15-20 minutes until the system becomes milky white, and then a toughening composition is added and stirred at 200-240 rpm for 5-10 minutes, and then the thermoplastic elastomer TPU resin pellets prepared in S1 are added and reacted at 180-240 rpm and 60-65° C. for 5-10 minutes, the temperature is raised to 88-95° C. and ultrasonic dispersion is performed, and the reaction is continued for 30-45 minutes under stirring at 180-240 rpm and ultrasonic dispersion, and deionized water is removed by vacuum distillation to obtain a semi-finished impact-resistant large-particle PMMA composite material;
[0051] S3, the semi-finished impact-resistant large-particle PMMA composite material is placed at 82-85° C. for heat treatment for 20-24 hours to obtain a finished impact-resistant large-particle PMMA composite material.
[0052] An acrylic sheet produced by using an impact-resistant large-particle PMMA composite material is prepared from the following raw materials in parts by mass: 10-20 parts of an impact-resistant large-particle PMMA composite material, 20-30 parts of an inorganic filler composition, 60-80 parts of methyl methacrylate, 1-5 parts of pentafluorophenyl methacrylate, 0.2-0.3 parts of dibenzoyl peroxide, 0.5-2 parts of gamma-methacryloxypropyltrimethoxysilane, and 1-4 parts of 1,6-hexanediol diacrylate.
[0053] The inorganic filler composition is composed of at least one of calcium carbonate, titanium dioxide, kaolin, aluminum hydroxide, and magnesium hydroxide and at least one of hollow glass microspheres, halloysite nanotubes, nanoalumina, and zinc oxide whiskers.
[0054] Preferably, the acrylic sheet is made of the following raw materials in parts by mass: 14-16 parts of impact-resistant large-particle PMMA composite material, 22-24 parts of inorganic filler composition, 65-70 parts of methyl methacrylate, 3-4 parts of pentafluorophenyl methacrylate, 0.25-0.3 parts of dibenzoyl peroxide, 1-1.5 parts of γ-methacryloxypropyltrimethoxysilane, and 3.0-3.5 parts of 1,6-hexanediol diacrylate.
[0055] The inorganic filler composition is composed of ultrafine calcium carbonate, ultrafine titanium dioxide, hollow glass microspheres with a particle size D50 of 25-50 microns, halloysite nanotubes, and zinc oxide whiskers. Preferably, the inorganic filler composition is composed of 2-5wt% zinc oxide whiskers, 20-40wt% hollow glass microspheres with a particle size D50 of 25-50 microns, 5-10wt% halloysite nanotubes, 5-20wt% ultrafine mixed crystal titanium dioxide, and the balance is ultrafine calcium carbonate.
[0056] A method for producing acrylic sheets using impact-resistant large-particle PMMA composite materials is as follows:
[0057] Step 1, preparation of impact-resistant large-particle PMMA composite material;
[0058] Step 2: Mix the inorganic filler composition, γ-methacryloxypropyltrimethoxysilane, and 1,6-hexanediol diacrylate to obtain a mixture A; and at the same time, mix methyl methacrylate, pentafluorophenyl methacrylate, and an impact-resistant large-particle PMMA composite material to obtain a mixture B;
[0059] Step 3, adding 40-60% of the total mass of dibenzoyl peroxide to the mixture B in step 2, mixing at 100-200 rpm for 5-10 min, heating to 80-85° C., mixing at 100-200 rpm for 25-40 min, and cooling to room temperature to obtain a PMMA prepolymer;
[0060] Step 4: Add mixed material A to the PMMA prepolymer and mix at 100-200 rpm for 30-60 minutes, cast it into a molding mold, ultrasonically vibrate it for 60-120 seconds, let it stand at room temperature for 0.5-1 hour, and then place it in an oven at 80-85°C for polymerization for 4-6 hours. Cool it, and demold it to obtain a high impact toughness acrylic sheet.
[0061] Example 1: An impact-resistant large-particle PMMA composite material includes a thermoplastic elastomer TPU resin as a core structure and a polymethyl methacrylate composite shell layer as a shell structure. The spherical thermoplastic elastomer TPU resin as the core structure contains unreacted double bonds and is connected to the polymethyl methacrylate composite shell layer as the shell structure through double bond polymerization.
[0062] The polymethyl methacrylate composite shell layer is made of 100 parts of methyl methacrylate MMA (CAS: 80-62-6), 5 parts of emulsifier 12-hexanoyloxy-9-octadecenoic acid (HOA), 100 parts of deionized water, 0.35 parts of dibenzoyl peroxide (CAS: 94-36-0), 3 parts of 2,2-diallyl-4-ene-1-amine (CAS No. 928836-00-4), 5 parts of 1,6-hexanediol diacrylate (CAS No. 13048-33-4), and 8 parts of toughening composition.
[0063] The toughening composition is composed of nano boron nitride nanosheets (boron nitride nanosheets, CAS: 10043-11-5, average thickness <100nm, brand Kemik), nano titanium nitride (average particle size 300-500nm, D50=395nm, CAS: 1344-2-2, brand Chaotai), zinc oxide whiskers (tetra-needle zinc oxide whiskers, CAS: 1344-2-2, diameter 0.5-5μm, length 10-50μm, item number XD-ZJX05, brand Chaotai), and halloysite nanotubes (haloysite nanotubes customized by Angxing New Carbon Materials Changzhou Co., Ltd., length 2-4μm, diameter 0.1-0.5μm). The mass ratio is 6:1.5:0.5:2.
[0064] The core-structured thermoplastic elastomer TPU resin is composed of 500.5g of 4,4'-diphenylmethane diisocyanate MDI (Yantai Wanhua), 144.2g of 1,6-hexanediol, 29.1g of 3-hexene-1,6-diol (CAS No. 67077-43-4), 190g of hydroxy-terminated polybutadiene (NISSO-PB G-2000), 500g of polycarbonate diol with a number average molecular weight of 2000 (1,6-hexanediol polyphenyl carbonate, analytical grade AR, Guangdong Wengjiang Chemical Reagent Co., Ltd.), 200g of polytetrahydrofuran diol with a number average molecular weight of 1000 (PTMEG, T-1000, Nantong Runfeng Petrochemical Co., Ltd.), 1.2g of bismuth octanoate (CAS No. 34364-26-6), 40g of toughening filler, 15g of antioxidant 1010, 1g of antioxidant 168, and 0.8g of inhibitor-4-methoxyphenol MEHQ.
[0065] The toughening filler is composed of nano-alumina (fumed alumina ALUNA-100 of Hubei Huifu Nanomaterials Co., Ltd.) and zinc oxide whiskers (tetrapod-shaped zinc oxide whiskers, CAS: 1344-2-2, diameter 0.5-5 μm, length 10-50 μm, item number XD-ZJX05, brand Chaotai) in a mass ratio of 19:1.
[0066] A method for preparing an impact-resistant large-particle PMMA composite material comprises the following steps:
[0067] S1, preparation of thermoplastic elastomer TPU resin with core structure: mix the chain extender and the polymerization inhibitor accounting for 25-40wt% of the total mass of the polymerization inhibitor and put them into the first feed tank of the twin-screw extruder; mix the polyol and the remaining polymerization inhibitor and put them into the second feed tank of the twin-screw extruder; mix the diisocyanate, catalyst, toughening filler and anti-aging agent and put them into the third feed tank of the twin-screw extruder; then extrude and granulate at 175-180°C, extrude, water-cool and granulate from the twin-screw extruder to obtain thermoplastic elastomer TPU resin pellets with an average particle size of 2-3mm;
[0068] S2, methyl methacrylate, emulsifier 12-hexanoyloxy-9-octadecenoic acid HOA, deionized water, dibenzoyl peroxide 2,2-diallyl-4-ene-1-amine, 1,6-hexanediol diacrylate are mixed and then subjected to high-speed shear treatment to obtain an emulsion, alkali solution is added dropwise to adjust the pH value to 9-9.2, the temperature is raised to 60° C. and reacted for 15 minutes until the system becomes milky white, and then the toughening composition is added and stirred at 200 rpm for 8 minutes, and then the thermoplastic elastomer TPU resin pellets prepared in S1 are added and reacted at 240 rpm and 65° C. for 10 minutes, the temperature is raised to 92° C. and ultrasonic dispersion is performed (ultrasonic frequency is 60 kHz, power is 800 W), the reaction is continued for 45 minutes under stirring at 240 rpm and ultrasonic dispersion, and deionized water is removed by reduced pressure distillation to obtain a semi-finished impact-resistant large-particle PMMA composite material;
[0069] S3, the semi-finished impact-resistant large-particle PMMA composite material is subjected to heat treatment at 85° C. for 24 hours to obtain a finished impact-resistant large-particle PMMA composite material.
[0070] An acrylic sheet produced by using an impact-resistant large-particle PMMA composite material comprises 15 parts of an impact-resistant large-particle PMMA composite material prepared in an embodiment, 24 parts of an inorganic filler composition, 66 parts of methyl methacrylate, 4 parts of pentafluorophenyl methacrylate (CAS: 13642-97-2), 0.3 parts of dibenzoyl peroxide, 1.5 parts of a γ-methacryloxypropyltrimethoxysilane KH570 coupling agent, and 3.2 parts of 1,6-hexanediol diacrylate (CAS: 13048-33-4).
[0071] The inorganic filler composition is composed of 5wt% zinc oxide whisker (tetrapod zinc oxide whisker, CAS: 1344-2-2, diameter 0.5-5μm, length 10-50μm, item number XD-ZJX05, brand Chaotai), 30wt% hollow glass microspheres with a particle size D50 of 50μm (hollow glass microspheres of Zhongke Huaxing New Materials-D2000, true density 0.3-0.36g / cm 3 , D 50 =50μm), 10wt% of halloysite nanotubes (customized by Angxing New Carbon Materials Changzhou Co., Ltd., length 2-4μm, diameter 0.1-0.5μm), 15wt% of ultrafine mixed crystal titanium dioxide (CAS:13463-67-7, average particle size 25nm, Angxing New Carbon Materials Changzhou Co., Ltd.), and 40wt% of ultrafine calcium carbonate (1250 mesh, light calcium carbonate, purchased by Jinan Boyang Chemical Co., Ltd.).
[0072] A method for producing acrylic sheets using impact-resistant large-particle PMMA composite materials is as follows:
[0073] Step 1, firstly preparing an impact-resistant large-particle PMMA composite material, and performing a reduced-pressure distillation treatment on the prepared impact-resistant large-particle PMMA composite material to remove the inhibitor component in the impact-resistant large-particle PMMA composite material;
[0074] Step 2, placing the inorganic filler composition, γ-methacryloxypropyltrimethoxysilane KH570 coupling agent, and 1.6-hexanediol diacrylate in a high-speed dispersing kettle and stirring at 500 rpm for 30 minutes under nitrogen protection to obtain a mixture A;
[0075] At the same time, methyl methacrylate, pentafluorophenyl methacrylate, and the impact-resistant large-particle PMMA composite material that has been subjected to vacuum distillation treatment in step 1 are placed in a reaction kettle, and magnetically stirred at 200 rpm for 30 minutes under nitrogen protection to obtain a mixture B;
[0076] Step 3, adding 60% of the total mass of dibenzoyl peroxide to the mixture B in step 2, stirring with a magnetic force at 120 rpm for 8 min, heating the mixture in a water bath to 85° C., stirring with a magnetic force at 160 rpm for 30 min, and cooling the mixture to room temperature to obtain a PMMA prepolymer;
[0077] Step 4: add the mixed material A in step 2 to the PMMA prepolymer obtained in step 3 and mix at 200 rpm for 30 min, evacuate to the autoclave pressure of 0.05 Pma, and perform vacuum degassing for 5 min. Introduce nitrogen into the reaction kettle to restore the normal pressure to obtain a casting material, and cast the obtained casting material into a molding mold. An ultrasonic generating probe is fixedly installed just below the bottom of the molding mold. After ultrasonic vibration at an ultrasonic frequency of 44 kHz / 1200 W for 100 s, let it stand at room temperature for 1.0 h, and then transfer it to an oven. Adjust the oven temperature to 85°C, perform polymerization for 4 h, cool, and demold to obtain a high impact toughness acrylic sheet.
[0078] The difference between Example 2 and Example 1 is that the polymethyl methacrylate composite shell layer is made of 80 parts of methyl methacrylate MMA, 4 parts of emulsifier 12-hexanoyloxy-9-octadecenoic acid HOA, 120 parts of deionized water, 0.30 parts of dibenzoyl peroxide, 1 part of 2,2-diallyl-4-ene-1-amine, 2 parts of 1,6-hexanediol diacrylate, and 5 parts of toughening composition.
[0079] The difference between Example 3 and Example 1 is that the polymethyl methacrylate composite shell layer is made of 80 parts of methyl methacrylate MMA, 6 parts of emulsifier 12-hexanoyloxy-9-octadecenoic acid HOA, 100 parts of deionized water, 0.30 parts of dibenzoyl peroxide, 4 parts of 2,2-diallyl-4-ene-1-amine, 10 parts of 1,6-hexanediol diacrylate, and 10 parts of toughening composition.
[0080] The difference between Example 4 and Example 1 is that the core-structured thermoplastic elastomer TPU resin is made of 500.5g of 4,4'-diphenylmethane diisocyanate MDI, 150.1g of 1,6-hexanediol, 29.1g of 3-hexene-1,6-diol, 228g of terminal hydroxyl polybutadiene NISSO-PB G-2000 with a number average molecular weight of 1900, 400g of polycarbonate diol (1,6-hexanediol polyphenyl carbonate) with a number average molecular weight of 2000, 180g of polytetrahydrofuran diol (PTMEG, T-1000) with a number average molecular weight of 1000, 1.2g of bismuth octanediate, 40g of toughening filler, 15g of antioxidant 1010, 1g of antioxidant 168, and 0.8g of inhibitor-4-methoxyphenol MEHQ.
[0081] The difference between Example 5 and Example 1 is that the core-structured thermoplastic elastomer TPU resin is made of 500.5g of 4,4'-diphenylmethane diisocyanate MDI, 141.8g of 1,6-hexanediol, 25.6g of 3-hexene-1,6-diol, 285g of terminal hydroxyl polybutadiene NISSO-PB G-2000 with a number average molecular weight of 1900, 500g of polycarbonate diol (1,6-hexanediol polyphenyl carbonate) with a number average molecular weight of 2000, 200g of polytetrahydrofuran diol (PTMEG, T-1000) with a number average molecular weight of 1000, 1.2g of bismuth octanediate, 40g of toughening filler, 15g of antioxidant 1010, 1g of antioxidant 168, and 0.8g of inhibitor-4-methoxyphenol MEHQ.
[0082] The difference between Example 6 and Example 1 is that the toughening composition is composed of nano-boron nitride nanosheets, nano-titanium nitride, zinc oxide whiskers, and halloysite nanotubes in a mass ratio of 6:0.5:0.5:2.
[0083] The difference between Example 7 and Example 1 is that the toughening composition is composed of nano-boron nitride nanosheets, nano-titanium nitride, zinc oxide whiskers, and amino-modified multi-walled carbon nanotubes (CAS: 1333-86-4, outer diameter 8-15nm, length 50μm, brand Xianfeng Naguang) in a mass ratio of 6:1.5:0.5:2.
[0084] The difference between Example 8 and Example 1 is that the toughening composition is composed of nano-boron nitride nanosheets, nano-titanium nitride, zinc oxide whiskers, and graphene nanosheets (CAS: 7440-44-0, sheet diameter: 5-10 μm, thickness: 3-10 nm, brand: Xianfeng Naguang) in a mass ratio of 6:1.5:0.5:2.
[0085] The difference between Example 9 and Example 1 is that the toughening composition is composed of nano-boron nitride nanosheets, nano-titanium nitride, and zinc oxide whiskers in a mass ratio of 6:3:1.
[0086] The difference between Example 10 and Example 1 is that an acrylic sheet produced using an impact-resistant large-particle PMMA composite material is made from 10 parts of the impact-resistant large-particle PMMA composite material prepared in Example 1, 30 parts of an inorganic filler composition, 65 parts of methyl methacrylate, 4 parts of pentafluorophenyl methacrylate, 0.3 parts of dibenzoyl peroxide, 1.5 parts of γ-methacryloxypropyltrimethoxysilane KH570 coupling agent, and 3.2 parts of 1.6-hexanediol diacrylate.
[0087] The difference between Example 11 and Example 1 is that an acrylic sheet produced using an impact-resistant large-particle PMMA composite material is made from 20 parts of the impact-resistant large-particle PMMA composite material prepared in Example 1, 20 parts of an inorganic filler composition, 65 parts of methyl methacrylate, 4 parts of pentafluorophenyl methacrylate, 0.3 parts of dibenzoyl peroxide, 1.5 parts of γ-methacryloxypropyltrimethoxysilane KH570 coupling agent, and 3.2 parts of 1.6-hexanediol diacrylate.
[0088] The difference between Example 12 and Example 1 is that an acrylic sheet produced using an impact-resistant large-particle PMMA composite material is made from 15 parts of the impact-resistant large-particle PMMA composite material prepared in Example 1, 24 parts of an inorganic filler composition, 69 parts of methyl methacrylate, 1 part of pentafluorophenyl methacrylate, 0.3 parts of dibenzoyl peroxide, 1.5 parts of γ-methacryloxypropyltrimethoxysilane KH570 coupling agent, and 3.2 parts of 1.6-hexanediol diacrylate.
[0089] The difference between Example 13 and Example 1 is that an acrylic sheet produced using an impact-resistant large-particle PMMA composite material is made from 15 parts of the impact-resistant large-particle PMMA composite material prepared in Example 1, 24 parts of an inorganic filler composition, 65 parts of methyl methacrylate, 5 parts of pentafluorophenyl methacrylate, 0.3 parts of dibenzoyl peroxide, 1.5 parts of γ-methacryloxypropyltrimethoxysilane KH570 coupling agent, and 3.2 parts of 1.6-hexanediol diacrylate.
[0090] The difference between Example 14 and Example 1 is that the inorganic filler composition is composed of 1250 mesh ultrafine calcium carbonate, 2000 mesh aluminum hydroxide (CAS: 21645-51-2), fumed alumina ALUNA-100, and tetrapod-shaped zinc oxide whiskers. The mass ratio of 1250 mesh ultrafine calcium carbonate, 2000 mesh aluminum hydroxide, nano-alumina, and tetrapod-shaped zinc oxide whiskers is 5:2:2:1.
[0091] The difference between Example 15 and Example 1 is that the inorganic filler composition is composed of 2000 mesh aluminum hydroxide (CAS: 21645-51-2), hollow glass microspheres, and halloysite nanotubes, wherein the mass ratio of 2000 mesh aluminum hydroxide, hollow glass microspheres, and halloysite nanotubes is 4:5:1.
[0092] The difference between Example 16 and Example 1 is that the inorganic filler composition is composed of 2wt% zinc oxide whiskers, 20wt% hollow glass microspheres with a particle size D50 of 50μm, 5wt% halloysite nanotubes, 5wt% ultrafine mixed crystal titanium dioxide, and the balance is ultrafine calcium carbonate.
[0093] The difference between Example 17 and Example 1 is that the inorganic filler composition is composed of 5wt% zinc oxide whiskers, 40wt% hollow glass microspheres with a particle size D50 of 50μm, 10wt% halloysite nanotubes, 20wt% ultrafine mixed crystal titanium dioxide, and the balance is ultrafine calcium carbonate.
[0094] The difference between Example 18 and Example 4 is that an acrylic sheet produced by using an impact-resistant large-particle PMMA composite material is made of 20 parts of the impact-resistant large-particle PMMA composite material prepared in Example 1, 20 parts of an inorganic filler composition, 66 parts of methyl methacrylate, 4 parts of pentafluorophenyl methacrylate, 0.3 parts of dibenzoyl peroxide, 1.5 parts of γ-methacryloxypropyltrimethoxysilane KH570 coupling agent, and 3.2 parts of 1.6-hexanediol diacrylate. The inorganic filler composition is composed of 5wt% zinc oxide whiskers, 40wt% hollow glass microspheres with a particle size D50 of 50μm, 10wt% halloysite nanotubes, 20wt% ultrafine mixed crystal titanium dioxide, and the balance is ultrafine calcium carbonate.
[0095] The difference between Example 19 and Example 4 is that an acrylic sheet produced by using an impact-resistant large-particle PMMA composite material is composed of 15 parts of the impact-resistant large-particle PMMA composite material prepared in the example, 30 parts of an inorganic filler composition, 66 parts of methyl methacrylate, 4 parts of pentafluorophenyl methacrylate, 0.3 parts of dibenzoyl peroxide, 1.5 parts of γ-methacryloxypropyltrimethoxysilane KH570 coupling agent, and 3.2 parts of 1.6-hexanediol diacrylate. The inorganic filler composition is composed of 5wt% of zinc oxide whiskers, 25wt% of hollow glass microspheres with a particle size D50 of 50μm, 10wt% of halloysite nanotubes, 15wt% of ultrafine mixed crystal titanium dioxide, 30wt% of ultrafine calcium carbonate, 10wt% of ammonium polyphosphate, and 5wt% of zinc borate.
[0096] Comparative Example
[0097] The difference between Comparative Example 1 and Example 1 is that an acrylic sheet produced using an impact-resistant large-particle PMMA composite material is made of 15 parts of TPU resin, 24 parts of 1250 mesh ultrafine calcium carbonate, 70 parts of methyl methacrylate, 0.3 parts of dibenzoyl peroxide, 1.5 parts of KH570 coupling agent, and 0.5 parts of bisphenol A bisallyl ether.
[0098] The TPU resin used in the acrylic sheet is prepared by melt extrusion granulation of BASF C65A HPM TPU resin, and its particle size is the same as that of the finished product of the impact-resistant large-particle PMMA composite material in Example 1.
[0099] A method for producing acrylic sheets using impact-resistant large-particle PMMA composite materials is as follows:
[0100] Step 1, placing 1250 mesh ultrafine calcium carbonate, γ-methacryloxypropyl trimethoxysilane KH570 coupling agent, and bisphenol A bisallyl ether in a high-speed dispersing kettle and stirring at 500 rpm for 30 minutes under nitrogen protection to obtain a mixture A;
[0101] At the same time, dibenzoyl peroxide was added to methyl methacrylate, and the mixture was stirred magnetically at 120 rpm for 8 min. The temperature in a water bath was raised to 85°C, and the mixture was stirred magnetically at 160 rpm for 30 min. The mixture was cooled to room temperature to obtain a PMMA prepolymer.
[0102] Step 2: Add the mixed material A in step 1 to the PMMA prepolymer obtained in step 1 and mix at 200 rpm for 30 minutes, evacuate to the autoclave pressure of 0.05 Pma, and perform vacuum degassing for 5 minutes. Nitrogen is introduced into the reaction kettle to restore the normal pressure to obtain a casting material, and the obtained casting material is cast into a molding mold, allowed to stand at room temperature for 1.0 hour, and then transferred to an oven, the oven temperature is adjusted to 85°C, the polymerization reaction is carried out for 4 hours, cooled, and demolded to obtain a high impact toughness acrylic sheet.
[0103] The difference between Comparative Example 2 and Comparative Example 1 is that: Step 2, add the mixed material A in step 1 to the PMMA prepolymer obtained in step 1 and mix at 200 rpm for 30 minutes, evacuate to the autoclave pressure of 0.05Pma, vacuum degassing for 5 minutes, introduce nitrogen into the reaction kettle to restore normal pressure to obtain a casting material, cast the obtained casting material into a molding mold, and fix an ultrasonic generating probe directly below the bottom of the molding mold. After ultrasonic vibration at an ultrasonic frequency of 44kHz / 1200W for 100s, let it stand at room temperature for 1.0h, then transfer it to an oven, adjust the oven temperature to 85°C, polymerize for 4h, cool, and demold to obtain a high impact toughness acrylic sheet.
[0104] The difference between Comparative Example 3 and Comparative Example 2 is that an acrylic sheet produced using an impact-resistant large-particle PMMA composite material is made of 15 parts of TPU resin, 24 parts of 1250 mesh ultrafine calcium carbonate, 66 parts of methyl methacrylate, 4 parts of pentafluorophenyl methacrylate, 0.3 parts of dibenzoyl peroxide, 1.5 parts of KH570 coupling agent, and 3.2 parts of 1.6-hexanediol diacrylate.
[0105] The difference between Comparative Example 4 and Comparative Example 2 is that an acrylic sheet produced using an impact-resistant large-particle PMMA composite material is made of 15 parts of TPU resin, 24 parts of the inorganic filler composition in Example 1, 70 parts of methyl methacrylate, 0.3 parts of dibenzoyl peroxide, 1.5 parts of KH570 coupling agent, and 0.5 parts of bisphenol A bisallyl ether.
[0106] The difference between Comparative Example 5 and Comparative Example 2 is that an acrylic sheet produced using the impact-resistant large-particle PMMA composite material is made of 15 parts of the impact-resistant large-particle PMMA composite material in Example 1, 24 parts of 1250 mesh ultrafine calcium carbonate, 70 parts of methyl methacrylate, 0.3 parts of dibenzoyl peroxide, 1.5 parts of KH570 coupling agent, and 0.5 parts of bisphenol A bisallyl ether.
[0107] The difference between Comparative Example 6 and Comparative Example 2 is that an acrylic sheet produced using the impact-resistant large-particle PMMA composite material is made of 15 parts of the impact-resistant large-particle PMMA composite material in Example 1, 24 parts of the inorganic filler composition in Example 1, 70 parts of methyl methacrylate, 0.3 parts of dibenzoyl peroxide, 1.5 parts of KH570 coupling agent, and 0.5 parts of bisphenol A bisallyl ether.
[0108] The difference between Comparative Example 7 and Example 1 is that the preparation method of the impact-resistant large-particle PMMA composite material is as follows:
[0109] S1, the TPU resin used is BASF C65A HPM TPU resin melt extruded and granulated to prepare TPU pellets with the same particle size as the finished impact-resistant large-particle PMMA composite material in Example 1;
[0110] S2, methyl methacrylate, emulsifier 12-hexanoyloxy-9-octadecenoic acid HOA, deionized water, dibenzoyl peroxide 2,2-diallyl-4-ene-1-amine, 1,6-hexanediol diacrylate were mixed and then subjected to high-speed shear treatment to obtain an emulsion, alkali solution was added dropwise to adjust the pH value to 9-9.2, the temperature was raised to 60°C and reacted for 15 minutes until the system was milky white, and then the toughening composition was added and stirred at 200 rpm for 8 minutes, and then the TPU pellets in S1 were added and reacted at 240 rpm and 65°C for 10 minutes, the temperature was raised to 92°C and ultrasonic dispersion was performed (ultrasonic frequency 60 kHz, power 800 W), the reaction was continued for 45 minutes under stirring at 240 rpm and ultrasonic dispersion, and the ionized water was removed by reduced pressure distillation to obtain a semi-finished impact-resistant large-particle PMMA composite material;
[0111] S3, the semi-finished impact-resistant large-particle PMMA composite material is subjected to heat treatment at 85° C. for 24 hours to obtain a finished impact-resistant large-particle PMMA composite material.
[0112] The difference between Comparative Example 8 and Example 1 is that the polymethyl methacrylate composite shell layer is made of 100 parts of methyl methacrylate MMA, 5 parts of emulsifier 12-hexanoyloxy-9-octadecenoic acid HOA, 100 parts of deionized water, 0.35 parts of dibenzoyl peroxide, 5 parts of bisphenol A bisallyl ether, and 8 parts of fumed alumina ALUNA-100.
[0113] The difference between the control group and comparative example 1 is that the acrylic sheet is made of 24 parts of 1250 mesh ultrafine calcium carbonate, 85 parts of methyl methacrylate, 0.3 parts of dibenzoyl peroxide, 1.5 parts of KH570 coupling agent, and 0.5 parts of bisphenol A bisallyl ether.
[0114] Mechanical properties test: Tensile strength is tested according to GB / T 1040-2006 "Test method for tensile properties of plastics". Flexural strength is tested according to GB / T 9341-2008 "Determination of flexural properties of plastics". Unnotched impact strength is tested according to GB / T 1043.1-2008 "Determination of impact properties of simply supported beams Part 1: Non-instrumented impact test".
[0115] Table 1: Test parameter table of acrylic sheet in Examples 1-19 and Comparative Examples 1-8
[0116]
[0117]
[0118]
[0119] It can be seen from Examples 1-19 and Comparative Examples 1-8 and Table 1 that the acrylic sheet prepared using the above-mentioned impact-resistant large-particle PMMA composite material has the advantages of good chemical corrosion resistance, weather resistance, easy cleaning and easy maintenance, as well as good impact resistance and toughness, antibacterial and mildew resistance, and light weight and high strength, which can meet the use requirements as a decorative panel.
[0120] The contact angle tests were performed on the acrylic sheets in Example 1 and Comparative Examples 2-3 respectively. It can be seen that the contact angle of the acrylic sheet in Example 1 is 95.3°, the contact angle of the acrylic sheet in Comparative Example 1 is 76.4°, and the contact angle of the acrylic sheet in Comparative Example 2 is 85.1°. It can be seen that the introduction of pentafluorophenyl methacrylate can improve the overall hydrophobic cleaning performance.
[0121] It can be seen from Example 1 and Example 19 and Table 1 that by optimizing and adjusting the formula of the inorganic filler composition, the impact toughness and mechanical strength of the prepared acrylic sheet are guaranteed, and the flame retardant properties of the acrylic sheet can be improved.
[0122] It can be seen from Example 1 and Comparative Examples 1-2 and Table 1 that the ultrasonic dispersion treatment in step 4 of the production process of the acrylic sheet can ensure the mechanical strength, impact toughness and flame retardant stability of the prepared acrylic sheet.
[0123] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An impact-resistant large-particle PMMA composite material, characterized in that: The impact-resistant large-particle PMMA composite material comprises a thermoplastic elastomer TPU resin as a core structure and a polymethyl methacrylate composite shell layer as a shell structure; The polymethyl methacrylate composite shell layer is made of the following raw materials in parts by mass: 80-100 parts of methyl methacrylate, 4-8 parts of emulsifier, 80-120 parts of deionized water, 0.2-0.35 parts of dibenzoyl peroxide, 1-4 parts of 2,2-diallyl-4-ene-1-amine, 1-10 parts of 1,6-hexanediol diacrylate, and 5-10 parts of toughening composition; The toughening composition is composed of at least one of nano boron nitride nanosheets, nano titanium nitride and zinc oxide whiskers, graphene, carbon nanotubes, and halloysite nanotubes; The thermoplastic elastomer TPU resin as the core structure contains unreacted double bonds, and is connected to the polymethyl methacrylate composite shell layer as the shell structure through double bond polymerization; the thermoplastic elastomer TPU resin with the core structure is at least one of spherical, quasi-spherical, and cylindrical; the thermoplastic elastomer TPU resin with the core structure is mainly made of diisocyanate, chain extender, polyol, catalyst, toughening filler, anti-aging agent, and inhibitor; The chain extender is composed of at least one of 1,4-butanediol, 3-methyl-1,5-pentanediol, and 1,6-hexanediol and at least one of 2,3-dihydroxy-1-butene, 4-cyclohexene-1,2-dimethanol, hexene-5-1,2-diol, 3-hexene-1,6-diol, 3-hexene-2,5-diol, and (9ci)-1-cyclohexene-1,3-diol; The polyol is composed of a hydroxy-terminated polybutadiene with a molecular weight of 500-2000 and at least one of a polycarbonate diol with a molecular weight of 1000-2000, a polyester diol with a molecular weight of 1000-2000, and a polyether diol with a molecular weight of 1000-2000; The total molar amount of the active functional groups contained in the chain extender and the polyol is equal to 1.0-1.02 times the molar amount of -NCO in the diisocyanate; The hard segment content of the thermoplastic elastomer TPU resin with the core structure is 40-46wt%; the catalyst is organic tin or organic bismuth; The toughening filler content is 4-8wt%; The toughening filler is composed of nano aluminum oxide and zinc oxide whiskers.
2. The impact-resistant large-particle PMMA composite material according to claim 1, characterized in that: The polymethyl methacrylate composite shell layer is made of the following raw materials in parts by mass: 100 parts of methyl methacrylate, 5-6 parts of emulsifier, 100 parts of deionized water, 0.30-0.35 parts of dibenzoyl peroxide, 2.8-3.2 parts of 2,2-diallyl-4-ene-1-amine, 4-6 parts of 1,6-hexanediol diacrylate, and 6-8 parts of toughening composition.
3. The impact-resistant large-particle PMMA composite material according to claim 1 or 2, characterized in that: The toughening composition is composed of nano boron nitride nano sheets, nano titanium nitride, zinc oxide whiskers and halloysite nano tubes.
4. The impact-resistant large-particle PMMA composite material according to claim 3, characterized in that: The mass ratio of the nano-boron nitride nanosheets, nano-titanium nitride, zinc oxide whiskers and halloysite nanotubes is 6:(0.5-2):(0.5-1):
2.
5. The impact-resistant large-particle PMMA composite material according to claim 1, characterized in that: A production process of an impact-resistant large-particle PMMA composite material comprises the following steps: S1, preparation of thermoplastic elastomer TPU resin with core structure: mix the chain extender and the polymerization inhibitor accounting for 25-40wt% of the total mass of the polymerization inhibitor and put them into the first feed tank of the twin-screw extruder; mix the polyol and the remaining polymerization inhibitor and put them into the second feed tank of the twin-screw extruder; mix the diisocyanate, catalyst, toughening filler and anti-aging agent and put them into the third feed tank of the twin-screw extruder; then extrude and granulate at 175-180°C, extrude, water-cool and granulate from the twin-screw extruder to obtain thermoplastic elastomer TPU resin pellets with a particle size of 0.5-5mm; S2, methyl methacrylate, emulsifier, deionized water, dibenzoyl peroxide 2,2-diallyl-4-ene-1-amine, and 1,6-hexanediol diacrylate are mixed and treated with high-speed shear to obtain an emulsion, alkali solution is added dropwise to adjust the pH value to 9-10, the temperature is raised to 60-65° C. and reacted for 15-20 minutes until the system becomes milky white, and then a toughening composition is added and stirred at 200-240 rpm for 5-10 minutes, and then the thermoplastic elastomer TPU resin pellets prepared in S1 are added and reacted at 180-240 rpm and 60-65° C. for 5-10 minutes, the temperature is raised to 88-95° C. and ultrasonic dispersion is performed, and the reaction is continued for 30-45 minutes under stirring at 180-240 rpm and ultrasonic dispersion, and deionized water is removed by vacuum distillation to obtain a semi-finished impact-resistant large-particle PMMA composite material; S3, the semi-finished impact-resistant large-particle PMMA composite material is placed at 82-85° C. for heat treatment for 20-24 hours to obtain a finished impact-resistant large-particle PMMA composite material.
6. An acrylic sheet produced using the impact-resistant large-particle PMMA composite material according to any one of claims 1 to 5, characterized in that: The acrylic sheet is made of the following raw materials in parts by mass: 10-20 parts of the impact-resistant large-particle PMMA composite material described in any one of claims 1 to 5, 20-30 parts of an inorganic filler composition, 60-80 parts of methyl methacrylate, 1-5 parts of pentafluorophenyl methacrylate, 0.2-0.3 parts of dibenzoyl peroxide, 0.5-2 parts of γ-methacryloxypropyltrimethoxysilane, and 1-4 parts of 1,6-hexanediol diacrylate; the inorganic filler composition is composed of at least one of calcium carbonate, titanium dioxide, kaolin, aluminum hydroxide, and magnesium hydroxide, and at least one of hollow glass microspheres, halloysite nanotubes, nanoaluminum oxide, and zinc oxide whiskers.
7. The acrylic sheet produced by using the impact-resistant large-particle PMMA composite material according to claim 6, characterized in that: The acrylic sheet is made of the following raw materials in parts by mass: 14-16 parts of the impact-resistant large-particle PMMA composite material described in any one of claims 1-5, 22-24 parts of an inorganic filler composition, 65-70 parts of methyl methacrylate, 3-4 parts of pentafluorophenyl methacrylate, 0.25-0.3 parts of dibenzoyl peroxide, 1-1.5 parts of γ-methacryloxypropyltrimethoxysilane, and 3.0-3.5 parts of 1,6-hexanediol diacrylate; the inorganic filler composition is composed of ultrafine calcium carbonate, ultrafine titanium dioxide, hollow glass microspheres with a particle size D50 of 25-50 microns, halloysite nanotubes, and zinc oxide whiskers.
8. The acrylic sheet produced by using the impact-resistant large-particle PMMA composite material according to claim 6 or 7, characterized in that: The inorganic filler composition is composed of 2-5wt% zinc oxide whisker, 20-40wt% hollow glass microspheres with a particle size D50 of 25-50 microns, 5-10wt% halloysite nanotubes, 5-20wt% ultrafine mixed crystal titanium dioxide, and the balance is ultrafine calcium carbonate.
9. The method for preparing a shock-resistant large-particle PMMA composite material according to claim 8, characterized in that: The method for producing an acrylic sheet using an impact-resistant large-particle PMMA composite material is as follows: Step 1, preparation of impact-resistant large-particle PMMA composite material; Step 2, mixing the inorganic filler composition, γ-methacryloxypropyltrimethoxysilane, and 1,6-hexanediol diacrylate to obtain a mixture A; and at the same time, mixing methyl methacrylate, pentafluorophenyl methacrylate, and the impact-resistant large-particle PMMA composite material according to any one of claims 1 to 6 to obtain a mixture B; Step 3, adding 40-60% of the total mass of dibenzoyl peroxide to the mixture B in step 2, mixing at 100-200 rpm for 5-10 min, heating to 80-85° C., mixing at 100-200 rpm for 25-40 min, and cooling to room temperature to obtain a PMMA prepolymer; Step 4: Add mixed material A to the PMMA prepolymer and mix at 100-200 rpm for 30-60 minutes, cast it into a molding mold, ultrasonically vibrate it for 60-120 seconds, let it stand at room temperature for 0.5-1 hour, and then place it in an oven at 80-85°C for polymerization for 4-6 hours. Cool it, and demold it to obtain a high impact toughness acrylic sheet.
Citation Information
Patent Citations
Calf weaner
CA94360A
Transparent TPU (thermoplastic polyurethanes) / PMMA (polymethyl (meth)acrylate) blends with improved low-temperature impact resistance
CN101291988A
Polyurethane and its complex substance in-situ modified polyvinyl chloride resin and preparing method
CN1743352A